About the conference ICAAM 2022. Preface - Ashyralyev, A.; Sadybekov, M. (Bulletin of the Karaganda University. Mathematics Series, 2023)
This issue is a collection of 13 selected papers. These papers are presented at the Sixth International Conference on Analysis and Applied Mathematics (ICAAM 2022) organized by Bahcesehir University, Turkey, Institute of Mathematics and Mathematical Modelling, Kazakhstan, and Analysis & PDE Center, Ghent University, Belgium. The meeting was held on October 31 – November 6, 2022, in Antalya, Turkey.